Strengthening ILP Standards Through Education And Simulation Of Diabetes Mellitus Screening Based On E- Health Center In Sukosari Village - Nabilah Ayu Ash-Shiddiqi; Dani Nasirul Haqi (International Journal of Health Engineering and Technology, 2026)
This increase in cases of diabetes mellitus as part of non-communicable diseases requires strengthening primary health care-based screening, including through optimizing the role of health cadres at the village level. However, the limited knowledge and skills of cadres are one of the obstacles in implementing early detection. This community service activity aims to improve the competence of cadres through the SINERGI (Simulation and Education for Diabetes Screening) program. The method used is descriptive quantitative with total sampling techniques on 27 health cadres who participated in the training. The evaluation was conducted through pre-tests and post-tests to measure changes in knowledge before and after the intervention. The results showed an increase in the average score from 46.29 (poor category) to 80 (good category), and 96% of cadres experienced an increase in their scores. These findings indicate that a combination of role-play-based education and simulation is effective in improving the capacity of cadres in diabetes mellitus screening at the village level.